Reactogenicity, safety and antibody response, after one and two doses of mRNA-1273 in seronegative and seropositive healthcare workers. Issue 2 (August 2021) - Tré-Hardy, Marie; Cupaiolo, Roberto; Papleux, Emmanuelle; Wilmet, Alain; Horeanga, Alexandra; Antoine-Moussiaux, Thomas; Della Vecchia, Andrea; Beukinga, Ingrid; Vekemans, Marc; Blairon, Laurent
Highlights: A single dose of mRNA-1273 appears to be sufficient in the vast majority of seropositive individuals prior to vaccination. Previously infected workers experienced more frequent and severe common side effects after the first dose. The second dose induced greater overall reaction than the first one regardless of the serological status.